VII International Congress of Innovation and Sustainable ICONIS (7th : 2023 Octubre 24 al 26 : Dubai, United Arab Emirates) - International Congress of Innovation and Sustainable ICONIS (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: International Conference on Innovation, Sustainability and Applied Sciences (ICISAS 2023) is a multi-professional conference dedicated to all applied specialised and interdisciplinary fields. It is a unique opportunity to learn from leading researchers and professionals on how to collectively shape the future through innovation, sustainability, and scientific vigor.